FORMULATION AND EVALUATION OF ATORVASTATIN CALCIUM NANOCRYSTALS CONTAINING P-GLYCOPROTEIN INHIBITORS FOR ENHANCING ORAL DELIVERY - LABIB, SARAH; NASR, MOHAMED; NASR, MOHAMED (International Journal of Current Pharmaceutical Research, 2021)
Objective: The main objective of this study was to develop atorvastatin calcium (ATR) as an oral drug delivery system for a P-glycoprotein (P-gp) substrate drug using different pharmaceutical excipients that inhibit P-glycoprotein and evaluate the influence of nanocrystals on the dissolution characteristics and bioavailability compared to the plain drug. Methods: A nanosuspension was prepared by Solvent-antisolvent precipitation method using a solvent containing stabilizer that act as a p-gp inhibitor dissolved in distilled water as polyethylene glycol 300, polyethylene glycol 400 (PEG 300, PEG 400), tween 20 and tween 80 while the solvent selected for atorvastatin calcium was methanol. The concentrations were as follows: PEG 300 and 400 = 0.25% w/v, tween 20 and 80 = 0.75% v/v. Nanocrystals were extracted from the suspension and characterized. Results: Particle size of the drug was 1307±127.79 nm while the formulas prepared ranged from 223±17.67 to 887±58.12 nm. Pure ATR had a saturated solubility of 0.059±0.005 mg/ml and the prepared nanocrystals ranged from 0.32±0.021 to 0.88±0.019 mg/ml. The Percentage of drug released of plain atorvastatin calcium reached 41.49% while the formula ranged from 44.32 to 61.5%. Both XRD and SEM discussed the degree of crystallinity as follows: F1<F2<F4<F3<ATR. Conclusion: 0.3% of PEG 300 and PEG 400 were not enough to formulate proper nanocrystals while 0.75% tween 20 and tween 80 achieved acceptable formulas. F4 which is prepared with tween 80 exhibited the highest enhancement in saturated solubility, dissolution rate and subsequently expected to have improved oral bioavailability.